A Comparative Study of Nutritional Content of SDD Drying Bedetan Perancak for Lemuru Fish Management in Jembrana, Bali: Studi Komparatif Kandungan Gizi Bedetan Perancak Hasil Pengeringan SDD untuk Pengelolaan Ikan Lemuru di Jembrana, Bali - I Wayan Darya Kartika; Putu Fery Karyada; Suprabadevi Ayumayasari Saraswati (Habitus Aquatica, 2026)
Bedetan Perancak is an innovative sardine processing product (cat sardine and protolan types) made by the Bedetan Perancak Women Farmers Group (KWT) in Jembrana Regency. It is dried using an eco-friendly Solar Dryer Dome (SDD) technology with a capacity of 200 kg per 3 days. This study compares the nutritional content of two Bedetan variants—unseasoned and seasoned—both dried using SDD. The analysis covers moisture, ash, protein, fat, carbohydrates (by difference), and estimated energy (kcal). Results indicate that moisture and ash are higher in the seasoned variant at 11.38% and 7.23%, respectively. Protein content is high in both variants: 62.89% (unseasoned) and 63.81% (seasoned). Fat content is similar, ranging between 15.03% and 15.13%. Carbohydrates are higher in the unseasoned variant (5.89%) than in the seasoned one (2.54%). Energy values are 411.30 kcal (unseasoned) and 400.70 kcal (seasoned). Adding seasoning affects moisture and ash but not protein and fat significantly. Both variants meet the SNI 8273:2023 standard for dried fish moisture (max 40%; ideal 15–20%), with moisture well below ideal limits. This shows that SDD technology is environmentally friendly and enhances nutritional quality and shelf life of Bedetan.